Hospital Information Systems (HIS) in the Examination Rooms and Wards: Doctors Perceived Positive Impact on Quality of Care and Patient Safety - Salahuddin, Lizawati; Ismail, Zuraini; ., . (International Journal of Engineering and Technology, 2018)
Hospital Information Systems [HIS] is developed to support healthcare organizations in providing efficient, quality, and safe healthcare services. The objective of this study is to identify and describe doctors’ perspective on the impact of HIS use in the examination rooms and wards on quality of care and patient safety. Semi-structured interviews were carried out with thirty one doctors from three Malaysian government hospitals. Thematic qualitative analysis was performed by using ATLAS.ti to deduce the relevant themes. HIS were commonly believed to improve quality of care and patient safety in terms of : [1] accessibility of patients’ record, [2] efficient patient-care, [3] well-structured report viewing, [4] less missing patients’ records, [5] legibility of patients’ records, and [6] safety features. In conclusion, the use of HIS in examination rooms and wards suggests to improve the quality of care and patient safety.